Exclusivity in licensing alliances: using hostages to support technology commercialization - Somaya, Deepak; Kim, Youngjun; Vonortas, Nicholas S. (Strategic Management Journal, 2011)
Abstract We examine why exclusivity provisions are used in licensing alliances, and when restrictions in licensing scope (e.g., by product or geography) accompany these exclusivity provisions. We find broad support for the proposition that these features are associated with the contractual challenges of allying with licensees when they contribute valuable complementary capabilities toward the commercialization of licensed technologies. Evidence from our data suggests that exclusivity is used as a contractual hostage to safeguard licensee investments in complementary assets and to enable contracting over early stage technologies. Scope restrictions are employed to balance the tradeoffs between the value creation made possible by licensee complementary capabilities and the transactional hazards entailed in working exclusively with licensees. Our results also suggest that scope restrictions and other formal safeguards may be substitute mechanisms for managing similar transactional concerns in licensing alliances. Copyright © 2010 John Wiley & Sons, Ltd.